2006
DOI: 10.1007/s10508-006-9060-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem, Risky Sexual Behavior, and Pregnancy in a New Zealand Birth Cohort

Abstract: This study examined the relationship between self-esteem in adolescence and later risky sexual behavior and pregnancy in late adolescence and early adulthood. The investigation analyzed data from a birth cohort of over 1,000 New Zealand young adults studied to the age of 25. Lower levels of self-esteem at age 15 were associated with greater risks of engaging in unprotected sex (sexual intercourse with either an opposite- or same-sex partner without using a condom), a greater number of sexual partners, and a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 48 publications
1
17
0
2
Order By: Relevance
“…A possible reason for the lack of association between sexual risk-taking and religion is the fact that, for most young people in Croatia, religion is an identity label, often merged with an ethno-national one, so religious values are rarely considered as guidelines for everyday conduct. The lack of association between self-esteem and sexual risktaking might be due to self-esteem having only weak or indirect effects on sexual risk-taking, as indeed suggested by recent studies (Abel & Chambers, 2004;Boden & Horwood, 2006). Unable to distinguish between indirect and direct effects, regression analysis cannot detect such an influence.…”
Section: Predictors Of Sexual Risk-takingmentioning
confidence: 89%
“…A possible reason for the lack of association between sexual risk-taking and religion is the fact that, for most young people in Croatia, religion is an identity label, often merged with an ethno-national one, so religious values are rarely considered as guidelines for everyday conduct. The lack of association between self-esteem and sexual risktaking might be due to self-esteem having only weak or indirect effects on sexual risk-taking, as indeed suggested by recent studies (Abel & Chambers, 2004;Boden & Horwood, 2006). Unable to distinguish between indirect and direct effects, regression analysis cannot detect such an influence.…”
Section: Predictors Of Sexual Risk-takingmentioning
confidence: 89%
“…Several possible mechanisms exist that could explain the relationship found in the current study between mental disorders and both early and past year sexual behavior. In general, these may include low self-esteem and a negative selfconcept which have overall been shown to be related both to engagement in sexual behaviors such as less condom use and more sexual partners, and to depression and suicidality in several countries (Boden & Horwood, 2006;Evans et al, 2005;Lejuez, Simmons, Aklin, Daughters, & Dvir, 2004;Sterk, Klein, & Elifson, 2004;Thatcher et al, 2002;Wild, Flisher, & Loombard, 2004). Additionally, a recent study in a Swedish sample found that individuals who engaged in high rates of ''impersonal sex'' (engaging in sex merely for the purpose of the act) were at increased likelihood of having ''adverse family backgrounds, a variety of negative health indicators, and dissatisfaction with life in general'' (Langstrom & Hanson, 2006, p. 49).…”
Section: Discussionmentioning
confidence: 99%
“…33,34 One pregnancy prevention study used a behavioral intervention to examine whether girls assigned to a behavioral treatment group relative to usual group care showed decreased pregnancy rates among juvenile justice girls. 35 This particular study found significant differences in post-baseline pregnancies between control and experimental groups, supporting the idea that behavioral-based techniques can be effective in reducing pregnancy; however, only 2 % of the study sample in this intervention was African American.…”
Section: Discussionmentioning
confidence: 99%